The effect of brand image and service quality on repurchase intention mediated by consumer destinations of Tangkelek distro in Bukittinggi city - Azihil Hamdi; Thamrin Thamrin (Universitas Negeri Padang, 2022)
The purpose of this study was to analyze the influence of Brand Image and Service Quality on Repurchase Intention through Consumer Satisfaction as a mediating variable. The sample in this study was the Tangkelek distribution in the city of Bukittinggi. The sampling technique in this study was non-probability sampling with a total sample of 151 respondents. The data used are primary data obtained from the results of respondents' responses to the proposed statement items. The results of this study indicate that: (1) Brand Image has a positive and significant effect on Repurchase Intention. (2) Service Quality has no significant effect on Repurchase Intention. (3) Consumer Satisfaction has a positive and significant effect on Repurchase Intention. (4) Brand Image has a positive and significant effect on consumer satisfaction. (5) Service Quality has a positive and significant effect on customer satisfaction. (6) Consumer Satisfaction acts as a partial mediating of the relationship between Brand Image and Repurchase Intention. (7) Consumer Satisfaction acts as a partial mediating of the relationship between Service Quality and Repurchase Intention.